PENGELOLAAN PEMBELAJARAN TAHFIZH DENGAN ISYARAT HIJAIYAH DALAM PENINGKATAN KEMAMPUAN MENGHAFAL AL-QUR’AN DI PONDOK PESANTREN TUNARUNGU DARUL ASHOM YOGYAKARTA - Aris Wintarso; Otong Surasman; Made Saihu (Lembaga Penelitian dan Studi kebijakan MADANI Instutute, 2023)
The management of Qur'an memorization (tahfizh) for deaf students requires a different approach compared to tahfizh education for regular students. Hearing impairment poses challenges in language acquisition and communication, making sign language an alternative method for tahfizh learning. This research aims to understand the management of tahfizh education for deaf students and the role of such management in enhancing the Qur'an memorization abilities of deaf students at Darul Ashom Deaf Boarding School in Yogyakarta. A qualitative approach was employed, focusing on planning, organizing, implementing, and evaluating the tahfizh learning process, as well as the function of management in improving the Qur'an memorization abilities of deaf students at Darul Ashom Deaf Boarding School in Yogyakarta. Data was collected through interviews, observations, and document analysis